The Great Debate Toward Conceiving the Fundamental Laws of The Universe, Revelation Against Experimentation - Alabdulgader, Abdullah (European Journal of Applied Sciences, 2025)
Exploring the intricate relationship between revelation and experimentation in understanding the fundamental laws of the universe is a mission that must be confronted in the current era. Through historical debates and modern scientific we discuss examples, which contrasts the materialistic approach of contemporary science with insights derived from spiritual revelation. The discussion emphasizes the limitations of human perception and highlights the need for an integrative approach that combines empirical investigation with spiritual wisdom, ultimately aiming to uncover deeper truths about existence and the cosmos.